Simultaneous arthroscopic cystectomy and unicompartmental knee arthroplasty for the management of partial knee osteoarthritis with a popliteal cyst: A case report - Liu, Cai; Zhou, Dejie; Liu, Xinwei; Huang, Jin; Fang, Jianguo; Zhou, Hongyu; Luo, Jianjun; Luo, Yiqian; Zhao, Lianghu (Frontiers in Surgery, 2023)
Introduction: Popliteal cyst is secondary to degenerative changes in the knee joint. After undergoing the total knee arthroplasty (TKA) and preserving the popliteal cyst, 56.7% of these patients who still presented with popliteal cysts at the mid-term (4.9 years) follow-up were still symptomatic in the popliteal area. The result of simultaneous arthroscopic cystectomy and unicompartmental knee arthroplasty (UKA) was uncertain. Case presentation: A 57-year-old man was admitted to our hospital with severe pain and swelling in his left knee and the popliteal area. He was diagnosed with severe medial unicompartmental knee osteoarthritis (KOA) with a symptomatic popliteal cyst in the left popliteal fossa. Then, arthroscopic cystectomy and unicompartmental knee arthroplasty (UKA) were performed simultaneously. A month after the operation, he returned to his normal life. There was no progression in the lateral compartment of the left knee and no recurrence of the popliteal cyst at the 1-year follow-up. Conclusions: For patients with a popliteal cyst seeking UKA, simultaneous arthroscopic cystectomy and UKA are feasible with great success if managed appropriately.